The political shortcut : the influence of corruption in Moldova - Panfil, Beatricie (2019)
Corruption is a major issue that can develop and grow in any country; it affects the principles of democracy and distorts the government institutions. The current work with the title “The Political Shortcut: The Influence of Corruption in Moldova” aims to research this phenomenon and its influence in Republic of Moldova. As the focus of the thesis is corruption, firstly the general features will be analyzed, followed by the analysis of the case study. Types and forms of manifestation of corruption are presented, alongside the factors that lead to the development of corruption. Anticorruption actions taken by authorities were analyzed and possible improvements of anticorruption activities were proposed. It was executed a multidimensional analysis from the economic and political perspective of corruption in the context of socioeconomic and political changes. The faults of the policies and government institutions were brought into light, thus the example of Moldova can serve as an illustration of the causes of development of corruption for other countries which are facing this problem.